Iron ore tailings in the production of cement tiles: a value analysis on building sustainability - Fontes, Wanna Carvalho; Fontes, Giovanni Gonçalves; Costa, Ellen Cristine Pinto; Mendes, Julia Castro; Silva, Guilherme Jorge Brigolini; Peixoto, Ricardo André Fiorotti (Ambiente Construído, 2018)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">The present work discloses the development of a sustainable cement tile (SCT) produced with Iron Ore Tailings from tailings dams (IOT). Initially, technical evaluation and environmental analysis of IOT were performed through physical, chemical and morphological characterisation, leaching and dissolution tests. Its feasibility as a pigment was also investigated. Subsequently, the value analysis was performed, starting from an empathy map to a study on environmental, social and emotional values in the relationship between people and product. As result, the IOT presented fine, crystalline particles, no toxicity, and is technically feasible to be employed as filler, aggregate and pigment in the production of SCT. The colour layer of the SCT presented more homogeneous colour and less pores than conventional ones. Therefore, the design of the SCT was developed, incorporating intangible values such as: environmental ideology, local identity and social expression. In this sense, the present work seeks to assist in the decision-making process involving IOT as construction material.